2011
DOI: 10.1007/s12098-010-0334-4
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Enterocolitis in a Term Neonate Following Intravenous Immunoglobulin Therapy

Abstract: A term baby with severe BO isoimmunization was treated with intravenous immunoglobulin. Shortly after the completion of the infusion, the baby developed clinical and radiological signs of necrotizing enterocolitis, with intestinal perforation and massive hemorrhagic ascites, resulting in the death of the baby.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The platelet count increase in the neonate (if it occurs) may take 24–72 h following IVIG infusion when given alone. Given limited data supporting its efficacy as an adjunct agent, as well as potential side effects from IVIG (including haemolysis in non‐group O neonates and neutropenia) (Majer & Green, ; Veys et al , ; Singh‐Grewal et al , ; Khan et al , ; Krishnan & Pathare, ; Luban et al , ; Akman et al , ), IVIG was not considered in addition to platelet transfusion.…”
Section: Resultsmentioning
confidence: 99%
“…The platelet count increase in the neonate (if it occurs) may take 24–72 h following IVIG infusion when given alone. Given limited data supporting its efficacy as an adjunct agent, as well as potential side effects from IVIG (including haemolysis in non‐group O neonates and neutropenia) (Majer & Green, ; Veys et al , ; Singh‐Grewal et al , ; Khan et al , ; Krishnan & Pathare, ; Luban et al , ; Akman et al , ), IVIG was not considered in addition to platelet transfusion.…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies have reported an association between IVIG administration and the development of NEC in neonates. Similar to septic infants, IVIG administration for NEC occurred in the first half of the study, before other studies reporting NEC as an adverse reaction to IVIG were published . Earlier publication of those findings may have influenced practice.…”
Section: Discussionmentioning
confidence: 98%
“…If clinicians do decide to order IVIG, whether within or outside of clinical guidelines, then the benefits and risks must be considered and discussed with the patient's family. IVIG is a blood product, and adverse events, including NEC and severe hemolysis, have been reported after its use. IVIG also potentially may cause hemolysis in nongroup O neonates, because IVIG contains anti‐A and anti‐B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…82,237 Our data do not reveal whether the association of NEC with isoimmunisation is linked with the condition itself or with its treatment. Case reports and retrospective studies have suggested that treatment of hemolytic anemia with intravenous immunoglobulins may precipitate NEC, 156,158 which is also counted among complications of exchange transfusion 106,238 but Roig and Burchfield reported two cases of NEC in infants with isoimmunisation before exchange transfusion. 239 Isoimmunisation is likely to predispose to general vulnerability and can be speculated to contribute to imbalance of the developing immune system, which might precipitate NEC.…”
Section: Risk Factorsmentioning
confidence: 99%